Moral betrayal of a leftist dream - Banerjee, Sumanta (2007)
A sense of public anger in West Bengal over Singur and Nandigram has not added up yet to a statewide agitation against the Left Front. The electorate is wise enough to recognise that there is no viable alternative as yet. But if the CPI(M) continutes to be obdurate, public outrage may take desperate forms. Reactionary forces like the Trinamool and BJP are waiting in the wings - the first such ominous signs were evident in Singur and Nandigram. - Reproduced.
Keywords: Agricultural land - India - West Bengal; Agricultural land